Pantun dan xintianyou : satu perbandingan - Tan, Xiao; Strategic Information and Research Development Centre (Petaling Jaya, Malaysia : Strategic Information and Research Development Centre, 2018)
History and criticism of Malay poetry and xintianyou, a folk music from Shaanxi province, China.
In Malay.
Keywords: Pantoums -- History and criticism; Quatrains, Malay -- History and criticism; Malay poetry -- History and criticism